オキゴンドウの水中鳴音について - Mizue, Kazuhiro; Takemura, Akira; Nakasai, kei (長崎大学水産学部, 1969)
The underwater sound of the false killer whale (Pseudorca crassidens) was-recorded at the sea area between Iki island and Tsushima island north-west of Kytighu as well as at the Shimonoseki Aquarium where the false killer whale had beeri kept since 1960. The recorded sound was analysed by the sound spectrograph. The false killer whale is taxonomically close to the killer whale (Orcinusow), but the feeding migration of the false killer whale in winter is mixed with the bottlenosed dolphin (Tursiops gilli) and also the underwater sound of the false killer whale bears a remarkable resemblance to that of the bottlenosed dolphin. The underwater sound of the false killer whale is divided into three types of signals, that is, whistle, clicks, and stratiform sound, and the function of these signals is the very same as that of the bottlenosed dolphin. The whistle is in the range from 5 to 10kc being identical to that of the bottlenosed dolphin. However, unlike in the bottlenosed dolphin, it is rather toneless and its sound spectorographic pattern is parallel to the abscissa. Next, the frequency of the clicks is not so high being within the limit below 13kc, but the repetition rate of the clicks is full of variety ranging from 2-per-second to 100-per-second. Finally, the stratiform sound which is observed at the time of feeding and in the course of courtship is the same as that of the bottlenosed dolphin. Generally speaking, these three types of signals are almost the same as those of the bottlenosed dolphin, but vary much more than the latter.!?1. The underwater sound of the false killer whales had been recorded since 1960 mainly at the Shimonoseki Aquarium and partly at the sea area of Iki-Tsushima. 2. The underwater sound of the false killer whales is roughly classified into three types of signals, i. e., whistle, clicks and stratiform sound. 3. Whistle of the talse killer whale is much the same as that of the bottlenosed dolphin, but with less intonation. 4. The false killer whale emits whistle together with clicks at ...